Research on flood sediments and rainstorm events in Huangtuwa, Northern Shaanxi - Shi, Hao; Yue, Dapeng; Zhao, Jingbo; Wang, Xiaoning (Frontiers in Environmental Science, 2023)
The research purpose of this paper is to reveal the relationship between flood deposits, rainfall and flooding in the Loess Plateau over the last 50 years. The research in this paper is of great significance as it reveals the torrential flood events and soil erosion in the central region of the Loess Plateau. Through grading analysis and 137Cs content determination of a closed lake sedimentary profile formed by landslide-blocked rivers in middle part of Loess Plateau, Zizhou County, Shaanxi Province, the age of the sedimentary formation in the section, as well as the rainstorm events and changes of soil erosion since 1954 are studied. The results show that the sediment particle size composition in the study section is fine, mainly comprising of coarse silt, while the content of sand particles (>100μm) is very low. The changes in137Cs content show that the sedimentary layer at a depth of 280–210cmin the research profile was formed between 1954 and 1964, while the deep sedimentary layer at 210–70cm was formed between 1965 and 1986 and the sedimentary layer above 70 cm depth was formed between 1987- and 2011. In total, 20 coarse particle layers (particle size > 50 μm) were deposited in the lake between 1954 and 2011.Thesedimentation timing of the 20 coarse particle layers was basically consistent with the timing of rainstorm events (daily rainfall ≥60 mm) in the study area, indicating that the coarse particle sediments in the lake represent rainstorm events. Soil erosion was stronger between 1954 and 1985 and was weaker after 1986.